2013
DOI: 10.1038/srep03264
|View full text |Cite
|
Sign up to set email alerts
|

Multiple leading edge vortices of unexpected strength in freely flying hawkmoth

Abstract: The Leading Edge Vortex (LEV) is a universal mechanism enhancing lift in flying organisms. LEVs, generally illustrated as a single vortex attached to the wing throughout the downstroke, have not been studied quantitatively in freely flying insects. Previous findings are either qualitative or from flappers and tethered insects. We measure the flow above the wing of freely flying hawkmoths and find multiple simultaneous LEVs of varying strength and structure along the wingspan. At the inner wing there is a singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 39 publications
2
33
0
Order By: Relevance
“…In both studies, a single LEV occurs at the inner wing and multiple LEVs were observed in the mid-wing region. Our results of LEV structure along the cicada wingspan are qualitatively consistent with these studies [24,32]. The cicada thorax-generated vortex was also found on the slice cut at the 15% spanwise location, indicating the importance of wing-body interactions in insects with a wide body.…”
Section: Leading Edge Vorticessupporting
confidence: 90%
See 2 more Smart Citations
“…In both studies, a single LEV occurs at the inner wing and multiple LEVs were observed in the mid-wing region. Our results of LEV structure along the cicada wingspan are qualitatively consistent with these studies [24,32]. The cicada thorax-generated vortex was also found on the slice cut at the 15% spanwise location, indicating the importance of wing-body interactions in insects with a wide body.…”
Section: Leading Edge Vorticessupporting
confidence: 90%
“…In some more recent studies, it was found that multiple LEVs were generated on the wings of real hawkmoths [24], and in a wing model of fruit fly [32]. In both studies, a single LEV occurs at the inner wing and multiple LEVs were observed in the mid-wing region.…”
Section: Leading Edge Vorticesmentioning
confidence: 95%
See 1 more Smart Citation
“…The dominating unsteady mechanism used in nature is the dynamic stall and associated LEV, which have been shown for many insects (Ellington et al, 1996;Birch and Dickinson, 2001;Sane, 2003;Johansson et al, 2013), and a few bird species (Muijres et al, 2012a, Warrick et al, 2009, Wolf et al, 2013. In this context, wind tunnel experiments of on-wing flow measurements of slow flying bats have demonstrated the presence of LEVs in the relatively small Palla's long-tongued bats ( ) the LEV contributes up to 40% of the total aerodynamic force (Table 1).…”
Section: U=4 M Smentioning
confidence: 96%
“…The flapping motion results in large geometrical AOA which would stall conventional translating wings. For flapping wings, generally, the flow starts to separate at the LE after wing reversals, and forms a LEV or LEVs [Johansson et al, 2013]. Instead of growing quickly and then shedding into the wake, the LEV on flapping wings generally remains attached over the entire half-strokes for two possible reasons: (1) the spanwise flow from the wing root to tip removes energy from the LEV which limits the growth and the shedding, as shown on Hawkmoth wings [Ellington et al, 1996]; and (2) due to the downwash flow induced by the tip and wake vortices, the effective AOA decreases and the growth of the LEV is restricted, as indicated by the wings of Drosophila [Birch & Dickinson, 2001].…”
Section: Formulationmentioning
confidence: 99%